2019
DOI: 10.1021/acs.nanolett.9b03194
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Real-Space Charge Transport Across a Donor–Acceptor Interface Mediated by Vibronic Couplings

Abstract: There is growing experimental and theoretical evidence that vibronic couplings, couplings between electronic and nuclear degrees of freedom, play a fundamental role in ultrafast excited-state dynamics in organic donor–acceptor hybrids. Whereas vibronic coupling has been shown to support charge separation at donor–acceptor interfaces, so far, little is known about its role in the real-space transport of charges in such systems. Here we theoretically study charge transport in thiophene:fullerene stacks using tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 54 publications
4
22
0
Order By: Relevance
“…Since this also affects PCEs, it needs to be considered when developing solar cells with higher efficiency. The observed photophysical process is consistent with previous experimental and theoretical results (6)(7)(8)(11)(12)(13)(14), which reported that this light-induced process takes place on the scale of tens of femtoseconds.…”
Section: Discussionsupporting
confidence: 91%
“…Since this also affects PCEs, it needs to be considered when developing solar cells with higher efficiency. The observed photophysical process is consistent with previous experimental and theoretical results (6)(7)(8)(11)(12)(13)(14), which reported that this light-induced process takes place on the scale of tens of femtoseconds.…”
Section: Discussionsupporting
confidence: 91%
“…The effective mass is calculated from the band structure of the system, which in turn can be determined using multiple methods, including the widely used tight-binding approximation method. 300 The relaxation time depends on the elastic scattering of the carriers with the defects as well as the lattice phonons.…”
Section: Charge Transport Through Molecular Arraysmentioning
confidence: 99%
“…According to the Boltzmann transport equation with relaxation-time approximation, the average mobility of the carrier in the band transport regime along an axis is given by where τ and m* are the components of second rank tensors of relaxation time and effective mass tensor along respective axes. The effective mass is calculated from the band structure of the system, which in turn can be determined using multiple methods, including the widely used tight-binding approximation method . The relaxation time depends on the elastic scattering of the carriers with the defects as well as the lattice phonons.…”
Section: Fundamental Charge Transfer and Transport Dynamicsmentioning
confidence: 99%
“…Open questions concern the dynamics of charge transfer and its transient regime in the ultrashort time window immediately following the laser perturbation. In studies performed on all-organic complexes, the coherent nuclear motion following the impulsive optical excitation was shown to be mainly responsible for the charge transfer at both covalently or non-covalently bound interfaces [65][66][67][68][69]. This scenario is intrinsically different from the charge-transfer excitons mentioned above, where the electron-hole separation results from the electronic structure of the material.…”
Section: Introductionmentioning
confidence: 99%